ANALISIS KAPASITAS DERMAGA TERMINAL PETIKEMAS MAKASSAR NEW PORT BERDASARKAN NILAI BERTH OCCUPANCY RATIO (BOR) DAN BERTH THROUGHPUT (BTP) - Putri, Khurin Wardana; Rahmawati, Annisa (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
Makassar New Port is a port in South Sulawesi located in the city of Makassar, South Sulawesi. Makassar New Port is one of the National Strategic Projects (PSN) built by PT Pelindo IV (Persero) and is one of the gateways for the import and export of goods through containers. Makassar New Port is an import and export shipping location with 362m long terminal facilities. The purpose of this study is to analyze the performance of Makassar New Port Container Terminal. Port performance can be measured from several factors, including the amount of equipment, the amount of cargo and containers moved, the loading and unloading time of containers, and the control at each port. In 2020, the yard capacity of Makassar New Port Container Terminal is still able to accommodate container traffic. This is based on the YOR analysis of 40.18% in 2020. For the terminal container handling system, the BOR in 2020 is 34.52%, the terminal utilization rate is still good, the BOR value is still below thae specified maximum value of 70%. Based on the calculation of terminal capacity, the Makassar New Port Container Terminal terminal capacity value is greater than the total container flow, so it can still handle the incoming container flow.